2015
DOI: 10.1016/j.apergo.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gait cadence on the ground reaction forces and plantar pressures during load carriage of young adults

Abstract: Biomechanical gait parameters--ground reaction forces (GRFs) and plantar pressures--during load carriage of young adults were compared at a low gait cadence and a high gait cadence. Differences between load carriage and normal walking during both gait cadences were also assessed. A force plate and an in-shoe plantar pressure system were used to assess 60 adults while they were walking either normally (unloaded condition) or wearing a backpack (loaded condition) at low (70 steps per minute) and high gait cadenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…However, the use of backpacks with heavy loads may induce several modifications in posture and gait, such as reduced pelvic rotation, increments in the head angle, a forward head position, and trunk flexion [2][3][4][5][6][7][8][9][10][11][12][13]. This may lead to adverse effects, such as increments in compression of intervertebral disks and in spine curvatures [1,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of backpacks with heavy loads may induce several modifications in posture and gait, such as reduced pelvic rotation, increments in the head angle, a forward head position, and trunk flexion [2][3][4][5][6][7][8][9][10][11][12][13]. This may lead to adverse effects, such as increments in compression of intervertebral disks and in spine curvatures [1,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, Castro et al [10] found greater normalized anterior-posterior and vertical GRFs (impact and thrust maximum) when the participants walked carrying a backpack at high cadences compared to walking with low cadences. Hence, testing the participants during their comfortable walking speed may be the cause of the nonsignificant increase in the normalized vertical GRFs.…”
Section: Discussionmentioning
confidence: 94%
“…This force represents the friction between the foot and shoe or shoe and ground, and its increase may lead to foot injuries [39] and a tendency to slip [12]. Both of the mentioned GRF components inform about the overall forces acting on the human body [10]. The vertical GRF increased almost three times in student carrying school bags weighing 20% of BW compared to 10% of BW [34].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the increase rate for maximum force on feet increases from 40 cm to 60 cm, and it is because the sole of shoe C is not fully compressed for 20 cm and 40 cm; because the viscos-elasticity dissipation pressure is bigger, and the sole is fully compressed when the height is 60 cm, so the influence of the sole viscos-elasticity on pressure will not increase, and then the redundant pressure will directly reach the feet (VanWassenhove et al, 2010). Besides, the maximum contact area of feet to sole is bigger when the sole is softer, and feet is a rugged hook face; only the front feet contacts the sole when feet touches the ground at the beginning, and the feet surface skin is compressed and deformed as pressure increases; the contact area of feet to the sole increases, and the sole is also compressed and deformed meanwhile (Castro et al, 2015); the deformation degree is greater when the sole is softer, so the contact area to the feet will increase. But the variation rule for maximum intensity of pressure and maximum pressure of sole is consistent, namely that the maximum intensity of pressure of the feet is smaller when the sole is softer.…”
Section: Discussionmentioning
confidence: 99%